Clinically suspected lethal viral myocarditis combined with encephalitis: a COVID‐19 vaccine complication - Junhui Chen; Ting Wu; Chunlei Zhang; Ye Zhang; Zhuanghua Liu; Yuhai Wang (ESC Heart Failure, 2023)
Abstract This case study aimed to identify rare viral myocarditis combined with encephalitis as a COVID‐19 vaccine complication. A 59‐year‐old male patient with a 2 day history of headache and rapidly progressive cognitive decline, who had received the third dose of COVID‐19 vaccine 12 days before, was admitted to our hospital. The patient had no underlying systemic conditions, no prior medical history, and no prior history of COVID‐19 infection. The patient was diagnosed with viral myocarditis and encephalitis by two neurologists and two cardiologists after laboratory examination, head computed tomography, and magnetic resonance imaging evaluation. The patient experienced cardiogenic shock and developed severe arrhythmia, resulting in his death 10 h after admission. Clinically suspected lethal viral myocarditis combined with encephalitis in the patient could be related to COVID‐19 vaccination. Adverse effects of the Chinese COVID‐19 vaccine, especially serious complications, have been uncommon. This case study highlights a rare complication after COVID‐19 vaccination that needs high attention.